2021
DOI: 10.4274/tao.2021.6180
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Features and Pathognomonic Sign of Stapes Footplate Fistula in Inner Ear Malformations

Abstract: Objective: Some inner ear malformations may cause recurrent meningitis, which may be fatal. The etiology is usually a stapes footplate fistula which enables microorganisms to pass into the inner ear containing cerebrospinal fluid (CSF), causing repeated attacks of meningitis. Radiological signs of the fistula are not obvious and are not reported in detail in the literature. The aim of the study is to investigate the radiological features of stapes footplate fistula in inner ear malformations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…In addition to autism – as in the present case – patients with dementia or severe developmental disorders are also considered to be at risk for the development of otogenic intracranial complications when they refuse treatment for otitis media. It is reported certain types of inner ear malformations (e.g., stapes footplate fistula) can cause recurrent meningitis [2]. However, the present patient had no inner ear malformation or fistula of the stapes footplate.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In addition to autism – as in the present case – patients with dementia or severe developmental disorders are also considered to be at risk for the development of otogenic intracranial complications when they refuse treatment for otitis media. It is reported certain types of inner ear malformations (e.g., stapes footplate fistula) can cause recurrent meningitis [2]. However, the present patient had no inner ear malformation or fistula of the stapes footplate.…”
Section: Discussionmentioning
confidence: 54%
“…In addition to this review article, there have been a few reports on labyrinthine fistulas without cholesteatoma. Regarding intracranial complications due to cochlear fistulae, Sennaroglu [2] reported that stapes footplate fistula can cause meningitis in cases with congenital inner ear malformations. However, no cases of acquired cochlear fistula with intracranial complications (e.g., meningitis or cerebral abscess) have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most commonly, these lesions are described with IP1 or common cavity anomalies (2,3). The nomenclature of lesions causing the bulging oval window sign on CT (3,4) has been discussed by Sennaroglu (2), who recognized that stapes footplate cyst is an inaccurate term, given that the contents of the lesion are not encapsulated but are in continuity with the perilymph space through the stapes footplate fistula. Although we have found no previous description of a round window cochleocele, a previous report of tympanotomy findings in a child with recurrent meningitis is suggestive of an earlier finding of this anomaly (5).…”
Section: Discussionmentioning
confidence: 99%
“…A fistula in the footplate may allow a fluid-filled pouch of endosteum to bulge into the middle ear space, referred to as a cochleocele, or, if open, allow leakage of CSF into the ear (1). Most commonly, these lesions are described with IP1 or common cavity anomalies (2,3). The nomenclature of lesions causing the bulging oval window sign on CT (3,4) has been discussed by Sennaroglu (2), who recognized that stapes footplate cyst is an inaccurate term, given that the contents of the lesion are not encapsulated but are in continuity with the perilymph space through the stapes footplate fistula.…”
Section: Discussionmentioning
confidence: 99%